Protein targeting to the plant vacuole - Neuhaus, Jean-Marc (My University, 1995)
Vacuolar proteins are synthesized in the endoplasmic reticulum and transported to the vacuole through the secretory pathway. Thee different types of vacuolar targeting peptides have been identified, either internal sequences or sequences carried by N- or C-terminal propeptides. These sequences differ from targeting determinants identified in other organisms. A putative sorting receptor for N-terminal targeting peptides has recently been identified. In contrast, little is known about the sorting of tonoplast proteins. Further work is needed to clarify the biogenesis of the plant vacuole.
Keywords: protein trafficking; propeptides; vacuole; tonoplast; sorting receptor